2021
DOI: 10.1021/acscatal.1c04442
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Conversion of Syngas to Higher Oxygenates over Tandem Catalysts

Abstract: Selective synthesis of higher oxygenates from syngas is an important but challenging research target, and the present methods for converting syngas into oxygenates suffer from low selectivity and high energy consumption in multiple processes. Herein, we report a tandem catalyst composed of carbon-supported CoMn and Rh-metalated 3v-PPh3-based porous organic polymers (POPs), which can convert syngas to oxygenates with a selectivity of up to 62.7% and where the percentages of C2+ and C6+ oxygenates exceed 96.6 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…The CO conversion levels over ZnZrO x with different Zn/Zr ratios were lower than 2.0% because of thermodynamic restriction (Figure c–e and Tables S3–S5). The typical millimeter-scale fixed-bed reactor is often considered a plug-flow reactor with little or no back-mixing of the flowing gas stream . However, an unconventional integration manner with the zeolite in the upstream bed and ZnZrO x in the downstream bed (the second manner in Figure a) showed that the conversion of syngas over ZnZrO x was significantly disturbed by zeolite (the second catalyst in Figure c–e); even the thickness of the quartz wool in-between was 3 mm.…”
Section: Resultsmentioning
confidence: 99%
“…The CO conversion levels over ZnZrO x with different Zn/Zr ratios were lower than 2.0% because of thermodynamic restriction (Figure c–e and Tables S3–S5). The typical millimeter-scale fixed-bed reactor is often considered a plug-flow reactor with little or no back-mixing of the flowing gas stream . However, an unconventional integration manner with the zeolite in the upstream bed and ZnZrO x in the downstream bed (the second manner in Figure a) showed that the conversion of syngas over ZnZrO x was significantly disturbed by zeolite (the second catalyst in Figure c–e); even the thickness of the quartz wool in-between was 3 mm.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the strong ability This journal is © The Royal Society of Chemistry 2022 of carbon chain growth, these catalysts presented higher selectivity to higher alcohols, but lower selectivity to ethanol. 222 For these multifunctional catalysts, the distances between the active sites (appropriate component proximity) are always the research focus. Lin et al reported that CO* or CH x O* insertion is the rate-determining step for C 2+ oxygenates.…”
Section: Multifunctional Catalystmentioning
confidence: 99%
“…Due to the strong ability of carbon chain growth, these catalysts presented higher selectivity to higher alcohols, but lower selectivity to ethanol. 222…”
Section: Direct Synthesis Of Ethanol From Syngasmentioning
confidence: 99%
“…Owing to the above limitations of direct conversion approaches, at present, the production of higher alcohols from syngas would inevitably rely on multi‐step processes comprising firstly the FTS of synthetic hydrocarbons enriched in linear olefins, followed by hydroformylation of the latter to the corresponding aldehyde derivatives with additional syngas, and finally aldehyde hydrogenation to alcohols, or reductive olefin hydroformylation (RHF) directly to alcohol end‐products [14] . While attractive as a process intensification strategy, the tandem integration of the FTS and olefin (R)HF conversion steps into a one‐pot transformation has long been impeded by incompatibility in process parameters such as operating temperatures [15] . Olefin‐producing FeC x ‐based FTS catalysts operate at temperatures >513 K, at which the molecular HF catalysts are not stable [5a, 16] .…”
Section: Introductionmentioning
confidence: 99%